Desenvolvimento de um método voltamétrico para determinação de N-nitrosodimetilamina em amostras de medicamentos - Nunes, Tassio de Araújo (2023)
At the end of 2021, an Anvisa ordinance warned of the possible presence of N-nitrosamines in sartana-type medications, which are a class of drugs widely used by patients to treat hypertension. N-nitrosamines are a group of organic compounds that present in their molecular structure (R2N-N=O) a nitroso group (-N=O) and an amine group (R2N-), where the substituent group R can be a group alkyl, aryl or aromatic. One of the N-nitrosamines that has been found in medicines is N-nitrosodimethylamine (NDMA), whose sources of contamination can occur in the synthesis process of the active ingredient, in the addition of excipients and in the packaging of the medicine. NDMA is a strong cancer-causing agent in various organs and tissues, such as the liver, brain, kidneys, stomach, bladder, lungs, esophagus, etc. High performance liquid chromatography (HPLC) has been widely used to determine NDMA in medicines. However, CLAE methods are laborious and slow, have a high consumption of solvents and reagents that are harmful to human health and a high cost of maintenance, operation and acquisition of equipment. These disadvantages can be overcome by voltammetric methods. Therefore, this work aimed to develop a new voltammetric method for the determination of NDMA in losartan and olmesartan samples, using a boron-doped diamond electrode. The method developed showed excellent accuracy (with recovery rates of 89.1 to 110.4%), reproducibility (with a relative standard deviation of 3.2%), detection limits (67.6 nmol L−1 NDMA) and quantification (225.3 nmol L−1 NDMA). The results obtained using the proposed method were compared with those obtained using a reference method (HPLC) and no statistically significant differences were detected between both results at a 95% confidence level. Therefore, the developed method can be considered a valuable alternative to other methods in the literature for determining NDMA in medicine.